1988
DOI: 10.1007/bf02380960
|View full text |Cite
|
Sign up to set email alerts
|

Black lemur (Lemur macaco) hand preference in food reaching

Abstract: ABSTRACT. The present study assessed the hand preferences exhibited by 33 black lemurs during routine feeding. Individual animals displayed hand preferences that were consistent across observations separated by as much as seven months. Within this population, 20 were left hand preferent, 12 right preferent, and 1 was ambidextrous. Correlational analysis of age and percentage left hand use indicated an inverse relationship in which younger animals tended towards the preferential use of the left hand and older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
3
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 11 publications
4
38
3
1
Order By: Relevance
“…laterality within a subject and within a task) or task specialization (i.e. laterality of function across subjects but within a task) (FoRSYTHE & WARD, 1988;MASATAKA, 1990). Manual specialization (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…laterality within a subject and within a task) or task specialization (i.e. laterality of function across subjects but within a task) (FoRSYTHE & WARD, 1988;MASATAKA, 1990). Manual specialization (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This might well explain the species-typical left-hand preferences displayed by primates that feed on insects using snatch and grab (i.e. ballistic) tactics, as in the case of prosimians (Forsythe & Ward 1988;Ward et al 1990), as well as the superior ability of the left hand for ballistic aimed movement in humans (Guiard et al 1983). The latter is also in keeping with the superior ability of the human right hemisphere for trajectory perception (Boulinguez et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In the latter study the subjects were tested for hand preference in food reaching from both bipedal and quadrupedal pos tures with the result that the manifestation of hand preference was linked to bipedal posture. Additional work by Ward's research group revealed evidence of reliable hand use preference for individuals of three additional prosimian species, Lemur catta, Lemur macaco and Varecia variegata variegata [9,19,28]. The majority of lemurs observed were determined to be left-hand-preferent in food reaching.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, three types of environmental constraints are covaried systemati cally across 8 tasks. Elevation of the target was se lected because of the effect of this variable on posture and the manifestation of prosimian hand preference in previous research [9,23].…”
Section: Introductionmentioning
confidence: 99%